The well-balanced leader : interactive learning techniques to help you master the 9 simple behaviors of outstanding leadership - Roberts, Ron, 1951- (McGraw-Hill, 2012)
In The Well-Balanced Leader, top experiential, accelerated-learning trainer Ron Roberts shows you how to identify your strengths and weaknesses in the nine most critical behavioral areas. He helps you "unstick" yourself from behavioral patterns that damage your influence as a leader, your relationships with those you lead, and the effectiveness of your organization.